ASPIRE Study: Results at Early Termination of LVR Study - Mosley, Mary (MD Conference Express, 2014)
A study of a nonsurgical lung volume reduction approach using an emphysematous lung sealant (ELS) demonstrated that >50% of treated patients experienced minimal, clinically important differences in health status and respiratory measures compared with patients treated only with optimal medical therapy. However, the rate of serious adverse events was higher in patients who responded to ELS treatment. The Study of the AeriSeal System for Hyperinflation Reduction in Emphysema [ASPIRE; NCT01449292; Washko GR et al. Am J Respir Crit Care Med 2014] was terminated early for financial reasons.